Learning to write, reading to learn : - Rose, David (South Yorkshire, 2012)
Suitable for practitioners, researchers and students, building up pedagogic, linguistic and social theory in steps, contextualized within teaching practice, this title presents the research of the 'Sydney School' in language and literacy pedagogy. It includes the genre-based writing pedagogy, genres across the school curriculum, and more.